Cholecystectomy in pregnant women with complicated biliary pathology at the Hospital de Clínicas - Zeoli, Mariana; Pontillo, Marcelo; Guillén, Alison; Tarigo, Nicolás; Delgado, Juan; Andreoli, Gustavo; Valiñas, Roberto (Cirugía del Uruguay, 2024)
The incidence of biliary pathology is high in our country; during pregnancy it is favored by hormonal and mechanical factors. Biliary pathology being the second cause of acute non-obstetric abdominal symptoms. The management of biliary complications is handled differently in our Hospital, especially with regard to indicating surgery during pregnancy. The objective was to compare the opportunity of cholecystectomy in pregnant women with complicated biliary pathology in our center versus the evidence at an international level. An observational, retrospective, cross-sectional and descriptive study was carried out in the period from January 1, 2017 to December 31, 2021, at the Hospital de Clínicas Dr. Manuel Quintela, Montevideo Uruguay. 57 patients were included. Average age 26 years. 81% manifested in the second and third trimester. The diagnoses were: acute cholecystitis (AC) in 28%; acute cholangitis 45.6%, acute pancreatitis (AP) 17.5% and symptomatic gallstones in 5.3%. 47% of the patients included in the study were not cholecystectomized at the time of data analysis. Only 30% of pregnant women were operated on. Conclusions: Only a third of pregnant women undergo cholecystectomy at the Hospital de Clínicas. The studies agree that cholecystectomy in pregnant women is safe in all trimesters; the treatment will be adjusted to each case according to the experience of the team and the resources of the environment.